Quality of life in chronic urticaria: A survey at a public university outpatient clinic, Botucatu (Brazil) - Silvares, Maria Regina Cavariani [UNESP]; Fortes, Maria Rita Parise [UNESP]; Miot, Hélio Amante [UNESP] (Elsevier, 2011)
Objective: To evaluate the impact of chronic urticaria on quality of life of outpatients through the university questionnaire Dermatology Life Quality Index (DLQI). Methods: Survey of the impact on quality of life caused by chronic urticaria, using the DLQI questionnaire validated for the Portuguese language. Patients were interviewed during visits to a specialized outpatient clinic between May 2009 and May 2010 at a Brazilian public service (Botucatu-SP). DLQI scores were analyzed according to the following subgroups: age, gender, education, disease duration, and presence of angioedema. Results: We interviewed 100 patients with chronic urticaria. There was a female predominance (86%), mean age 41.8 years, mean disease duration of 6 years, and angioedema occurrence in 82% of patients. The mean DLQI score was 13.5, characterized by serious impact on quality of life, higher than Hansen's disease, psoriasis, atopic eczema, and basal cell carcinoma. The presence of angioedema was associated with higher scores: 14.5 x 9.9 (p < 0.01). Female patients reported greater impact on clothing, while male patients reported treatment interference with work and study (p < 0.05). Conclusion: Chronic urticaria seriously compromises the quality of life of patients evaluated at a university service in Brazil, particularly of patients with angioedema. © 2011 Elsevier Editora Ltda.
Keywords: Angioedema; Quality of life; Quality of life index; Sickness impact profile; Urticaria